Comparison of Histopathological Findings with Duplex Sonography of the Temporal Arteries in Suspected Giant Cell Arteritis - Pfenninger, L.; Horst, A.; Stuckmann, G.; Flury, R.; Stürmer, J. (Klinische Monatsblätter für Augenheilkunde, 2012)
Introduction: In clinical practice the temporal artery biopsy (TAB) in suspected giant cell arteritis (GCA) is still believed to be the “gold standard”. The purpose of this study was to compare the histopathological findings of the TAB with duplex sonography of the temporal artery.Patients and Methods: In our retrospective study we analysed 85 consecutive patients (52 female, mean age 71.5, range 55 – 91 years; 33 male, mean age 71.6, range 44 – 91 years) with suspected GCA who underwent TAB in our clinic between January 1999 – February 2011. All patients received a preoperative duplex sonography, 57 patients including description of the temporal arteries.Results: 38 of 85 (44.7 %) of the artery biopsies were proven positive for GCA by histopathology. Interpretation of the duplex sonography was congruent of histopathological interpretation of the biopsy in 39 patients (68.4 %) and incongruent in 18 patients (31.6 %). Sensitivity of duplex-sonography was 44.4 %, specificity 90 %, positive predictive value 80 %.Discussion: Duplex sonography is a non-invasive and very helpful diagnostic tool to guide the clinician in cases of suspected GCA but needs considerable skills. It shows a good specificity and relatively high positive predictive value as there are only few false positive results. A negative report however does not rule out GCA, so that in our opinion the TAB – at least in those cases – should still be performed.
Keywords: giant cell arteritis; temporal artery; biopsy; duplex sonography